Effect of Exogenous Factors on Bacteriocin Production from Lactobacillus paracasei J23 by Using a Resting Cell System - Yi, Huaxi (Molecular Diversity Preservation International (MDPI), 2013)
A resting cell system was developed for bacteriocin Lac-B23 production from Lactobacillus paracasei J23. The resting cell medium contained (g/L): Glucose 20, Sodium acetate 5.0, MnSO(4) 0.25 MgSO(4) 0.5, Ammoniumhydrogencitrate 1.0, KH(2)PO(4) 1.0. The resting cell incubation time and temperature were 20 h and 37 °C and the effects of exogenous factors, including amino acids, glycerol, pyruvic acid, and α-ketoglutaric acid were investigated. Cys and Gly could stimulate the production of bacteriocin, while no stimulus effect was observed for Glu, Tyr and Ala. Glycerol and pyruvic acid increased bacteriocin production and the optimum concentrations were 1% and 30 g/L, respectively. Bacteriocin could act as an inducer of its own biosynthesis. These findings are of importance for the further study of bacteriocin biosynthesis regulation and for the improvement of bacteriocin production yields.